2018
DOI: 10.1002/prca.201800162
|View full text |Cite
|
Sign up to set email alerts
|

The Platelet Releasate is Altered in Human Pregnancy

Abstract: Purpose: Healthy pregnancy is characterized by an increase in platelet activation and a decrease in the number of circulating platelets with gestation. Despite this recognized importance, proteomic studies investigating platelets in healthy pregnancy have not been performed. As platelet cargo can be altered in different conditions, it is hypothesized that platelets may store a relevant and bespoke collection of molecules during pregnancy. Experimental design: Comparative label-free quantitative proteomic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Increasing platelet count is one way to protect the body from the development of gestational diabetes in pregnant animals (Yang et al, 2015). It is known that physiological pregnancy is characterized by an increase in platelet activation and a decrease in the total number of circulating platelets (Szklanna et al, 2019). The value of thrombocrit in the pregnant rats increased, which is due to an increase in platelet count in the pregnant rats of group II.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing platelet count is one way to protect the body from the development of gestational diabetes in pregnant animals (Yang et al, 2015). It is known that physiological pregnancy is characterized by an increase in platelet activation and a decrease in the total number of circulating platelets (Szklanna et al, 2019). The value of thrombocrit in the pregnant rats increased, which is due to an increase in platelet count in the pregnant rats of group II.…”
Section: Discussionmentioning
confidence: 99%
“…Intact platelets and the platelet clot were carefully removed by centrifuging sequentially x3 at 1000 × g for 10 min at 4°C (in the presence of 2% protease and 2% phosphatase inhibitors; Roche) and harvesting the supernatant each time. The final spin yielded the activated PR as before ( 7 , 16 , 21 , 22 ), which was stored at −80 °C until further use.…”
Section: Methodsmentioning
confidence: 99%
“…84,85 Indeed, recent data have demonstrated that specific proteomic and genomic EV profiles discriminate between various physiological and pathological states (e.g., pregnant vs. non-pregnant state) and as such may represent an avenue for novel diagnostics/predictive models in different diseases. [86][87][88][89] The contents of distinct EV populations not only have the potential to act as a 'barcode' for disease but also mediate important signalling activities and have been shown to regulate numerous physiological and pathological processes. 85,[90][91][92] Specific EV profiles have been described in preeclampsia and appear to play an important role in the progression of this disorder.…”
Section: Derangements Of Blood Coagulation and Fibrinolysis In Preeclmentioning
confidence: 99%